Higher Education Reform in Lithuania: Achievements and Problems - Želvys, Rimantas; Žilinskaitė, Rima (Acta Paedagogica Vilnensia, 2004)
The purpose of the article is to review and analyse the ongoing higher education reform in Lithuania. Changes in Lithuanian higher education began when the country regained its independence in 1990. The process of reforming the sector of higher education led to a number of significant achievements; however, certain important problems still remain unsolved. The aim of our research was to highlight both major achievements and remaining problems. We chose eight important areas: legal basis of higher education; the network of higher education institutions; reforming the structure of studies; financing higher education; international cooperation; higher education reform strategy; programs and projects linked with higher education reform; quality assurance in higher education. The main conclusion of our analysis is that higher education reform is a typical example of decentralized reform, which, on one hand, provides more opportunities for educational institutions to find their own ways of development; on the other hand, decentralized reform is much more difficult to manage, monitor and assess its long-term sustainable effect.